Decentralization, citizen participation and local public service delivery: A study on the nature and influence of citizen participation on decentralized service delivery in Kenya - Abraham Rugo Muriu (Universitätsverlag Potsdam, 2013)
Governments at central and sub-national levels are increasingly pursuing participatory mechanisms in a bid to improve governance and service delivery. This has been largely in the context of decentralization reforms in which central governments transfer (share) political, administrative, fiscal and economic powers and functions to sub-national units. Despite the great international support and advocacy for participatory governance where citizen's voice plays a key role in decision making of decentralized service delivery, there is a notable dearth of empirical evidence as to the effect of such participation. This is the question this study sought to answer based on a case study of direct citizen participation in Local Authorities (LAs) in Kenya. This is as formally provided for by the Local Authority Service Delivery Action Plan (LASDAP) framework that was established to ensure citizens play a central role in planning and budgeting, implementation and monitoring of locally identified services towards improving livelihoods and reducing poverty. Influence of participation was assessed in terms of how it affected five key determinants of effective service delivery namely: efficient allocation of resources; equity in service delivery; accountability and reduction of corruption; quality of services; and, cost recovery. It finds that the participation of citizens is minimal and the resulting influence on the decentralized service delivery negligible. It concludes that despite the dismal performance of citizen participation, LASDAP has played a key role towards institutionalizing citizen participation that future structures will build on. It recommends that an effective framework of citizen participation should be one that is not directly linked to politicians; one that is founded on a legal framework and where citizens have a legal recourse opportunity; and, one that obliges LA officials both to implement what citizen's proposals which meet the set criteria as well as to account for their actions in the management of public resources.
Advisor: Proeller, Isabella; Advisor: Jann, Werner; urn:nbn:de:kobv:517-opus-65085
Keywords: 650; decentralization; citizen participation; local public service delivery; Kenya